Teacher's guide : from the Devine Entertainment video series - Henderson, Betsy; Bach, Johann Sebastian, 1685-1750.; Handel, George Frideric, 1685-1759.; Rossini, Gioacchino, 1792-1868.; Liszt, Franz, 1811-1886.; Strauss, Johann, 1825-1899.; Bizet, Georges, 1838-1875.; Hal Leonard Publishing Corporation (Milwaukee, WI : Devine Entertainment : Hal Leonard, 2000)
Offers lesson plans to accompany the video stories of Bach, Handel, Rossini, Liszt, Strauss and Bizet.
Bach's fight for freedom -- Handel's last chance -- Rossini's ghost -- Liszt's rhapsody -- Strauss: the king of three-quarter time -- Bizet's dream.
Includes bibliographical references (p. 98-99).
Keywords: Composers -- Instruction and study; Teaching -- Aids and devices